The real exchange rate policy trilemma in developing economies - Arslan Razmi (University of Massachusetts, Department of Economics, 2018)
This paper discusses some of the inter-temporal issues that arise in the pursuit of real undervaluation to achieve rapid development. Policy makers face a trade-off between achieving a capital stock target in a given amount of time on the one hand and boosting real wages and output in the short run, on the other. This generates a trilemma whereby development-focused policy makers can choose to pursue two out of three desirables: (1) use the real exchange rate as an instrument of development policy, (2) meet the development target within a politically relevant time frame, and (3) maintain political stability. The optimal path under a policy with "unambitious" aims will resemble the typical electoral business cycle trajectory whereby policy makers maintain real overvaluation over much of the cycle. By contrast, achieving relatively ambitious capital stock targets within a relatively short time requires the potentially unpopular strategy of choosing a highly undervalued real exchange rate at the beginning of the planning horizon and gradually increasing the degree of undervaluation thereafter as wages rise. Relevant structural differences between countries imply different initial levels of real undervaluation, distinct optimal trajectories over time, and hence, varying degrees of political trade-offs.
Keywords: O11; O25; F43; 330; Real exchange rate; development; political business cycles; optimal policy; capital accumulation